2018
DOI: 10.1111/jasp.12548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valenced vicarious online contact on out‐group prejudice and perceived out‐group variability: A study of online poker

Abstract: Online poker has become a multibillion dollar industry, with millions of people from around the world both playing and watching online poker each year. Unlike live poker, players and watchers, typically cannot rely on physical cues of other players; in fact, the only information often available to poker players is others’ nationality. Because these poker games often involve members of different national groups, it constitutes a context of indirect contact that has considerable potential to examine how attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…With respect to vicarious contact, Joyce and Harwood (2014) showed that observing a positive (vs. negative or neutral) intergroup interaction generalized to more positive attitudes toward secondary outgroups by means of attitude generalization. Andrews (2018) tested the effects of observing a positive, a negative, or a neutral interaction between an ingroup poker player and a Russian (outgroup) player among New Zealand participants. Attitudes toward Chinese people—the secondary outgroup—were more positive in the positive versus the negative and neutral conditions (but no STE emerged for the secondary outgroups of Arabs or Americans).…”
Section: Indirect Intergroup Contactmentioning
confidence: 99%
“…With respect to vicarious contact, Joyce and Harwood (2014) showed that observing a positive (vs. negative or neutral) intergroup interaction generalized to more positive attitudes toward secondary outgroups by means of attitude generalization. Andrews (2018) tested the effects of observing a positive, a negative, or a neutral interaction between an ingroup poker player and a Russian (outgroup) player among New Zealand participants. Attitudes toward Chinese people—the secondary outgroup—were more positive in the positive versus the negative and neutral conditions (but no STE emerged for the secondary outgroups of Arabs or Americans).…”
Section: Indirect Intergroup Contactmentioning
confidence: 99%
“…Findings from these studies parallel those of direct contact, showing that negative contact has detrimental effects on intergroup relations that are opposite to the effects of positive contact (Graf & Paolini, 2017). Specifically, negative, in contrast to positive, vicarious contact has been found to negatively impact on outgroup attitudes (Andrews et al., 2018; Castelli et al., 2012; Joyce & Harwood, 2014).…”
Section: Media Vicarious Contactmentioning
confidence: 99%
“…Even the vicarious observation of a positive interaction between online poker players from different national groups online increases positive attitudes towards the outgroup. In this study, the reverse was also true, where witnessing negative interactions led to more negative attitudes towards the outgroup [30].…”
Section: Contact Quality Valence and Prejudicementioning
confidence: 50%
“…Many studies, however, examined the effect of positive contact versus the absence of contact [10,[27][28][29]. A few studies have found that when compared, negative contact increases prejudice, while positive contact plays a restorative role and decreases prejudice [6,30].…”
Section: Contact Quality Valence and Prejudicementioning
confidence: 99%